Pengaruh Environmental Disclosure Quality Terhadap Firm Performance Dimoderasi Oleh Board Independence - Livia Marcellina Tanujaya; Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to obtain empirical evidence on the effect of the quality of environmental disclosure on company performance as moderated by the existence of the company's independent board of commissioners in manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The research design used to examine the effect of the independent variables on the dependent variable through moderating variables is a descriptive study with a purposive sampling method and resulted in 261 sample. To test the hypothesis, the panel data regression model is used. Data processing in this study uses the Eviews version 10. The results show that the quality of the company's environmental disclosure does not have a significant effect on company performance, but the quality of environmental disclosure has a positive effect on company performance. This study also shows that the proportion of the company's independent board of commissioners has a significant moderating effect to strengthen the relationship between the quality of environmental disclosure on company performance. The implication of this research is to improve corporate governance mechanisms, especially in the structure and proportion of independent boards of commissioners which turns out to be important in strengthening the relationship between environmental disclosure quality and firm performance.